Parenting Through Piil Pesenggikhi Values of Lampung Culture for Early Childhood Moral Development - Utama, Ferdian; Arif, Mahmud; Maharsi, Maharsi (COUNS-EDU: The International Journal of Counseling and Education, 2023)
This research aims to reveal how piil pesenggikhi develops and becomes a family parenting pattern for the Lampung people. Piil pesenggikhi is taught by parents from early childhood through the family environment. However, immoral behaviours are still committed by children from Lampung community families. The problem formulation presented is how parents teach their children these values for early childhood moral development. This research uses qualitative methods to examine Lampung community families and traditional Lampung elders. Researchers found a specific identity from the values of piil pesenggikhi, including nemui nyimah, juluk adok, nengah nyappor, and sakai sambayan. Through these values, early childhood moral development is carried out through learning that prioritizes respect, courtesy, hospitality, acceptance of differences, perseverance, and teaching children to help each other.